Mixture of Indonesian White Portland Cements, Bi2O3, and Light Cured Methacrylate-based resin as a potential candidate for pulp capping material - Nurdin, Denny; Simanjuntak, Beactris Lamria; Farah Adang, Rahmi Alma; Cahyanto, Arief (Faculty of Dentistry Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The bioactivity property of pulp capping materials is determined by the hydroxyl ion release ability, which may alter the environmental pH to become alkaline. Calcium silicate-based materials are antibacterial, able to induce reparative dentin and have a good bacteria-tight seal. The poor handling of calcium silicate-based materials can be overcome by adding resin, so the materials will be easier to handle. Therefore, the purpose of this study was to synthesize a mixture of Indonesian White Portland Cements, Bi2O3, Light Cured Methacrylate-based Resin and analyze its hydroxyl ion release ability. Methods: The study wasquasi experimental. Sample in this research is the Indonesian White Portland Cements. The Indonesian White Portland Cements, Bi2O3 mixture was prepared using the simple solution method and mixed with Light Cured Methacrylate-based Resin. Population was WPC, Bi2O3 and light cured methacrylate-based resin. The sample’s ability to release hydroxyl ions was measured using a calibrated pH meter and titration test 60, 120, 180 and 320 minutes. Analyzed Results: This study showed that the mixture of Indonesian White Portland Cements, Bi2O3, Light Cured Methacrylate-based Resin had an initial pH of 11.04 and increased to its peak on 168 hours mark, or on day seven, to pH 11,77 with hydroxyl ion release value of 10-2.23 Conclusions: The mixture of Indonesian White Portland Cements, Bi2O3, Light Cured Methacrylate-based Resin has an alkaline pH, is able to release hydroxyl ion and has a potential candidate for pulp capping material.Keywords :Indonesia white portland cements, Bi2O3, light cured methacrylate-based resin, hydroxyl ion release ability